Helsekulturer" Hvordan kan sykepleiestudenter øke sin kulturkompetanse? - Inger- Lise Magnussen (Septentrio Academic Publishing, 2013)
Abstract "Health cultures" How can nursing students improve their knowledge about different cultures? A learning project for nursing students and multilingual students in high school. Norway is a multicultural society, and the need for knowledge about different cultures will be present in several professions, including nursing. During practice, nursing students will most probably meet immigrants, either as a colleague or a patient. Do students have enough knowledge about their cultural background, and how can this knowledge be acquired? Is it possible to create "cultural meetings" when they are in practice, so nursing students can get to know different cultures during their education? Working together with multilingual students in high school can be a way to create cultural meetings. Such cooperation can provide mutual learning, community and integration. The learning project "Health Cultures" is based on cultural meetings and uses project as learning method. The project is conducted while students are in practice in municipal health services.